Plasmids prevalence and patterns in diarrheagenic Escherichia coli reflect the bacterial transmission possibility - Noor Almousawi; Murtakab Al-Hejjaj (Basrah Journal of Veterinary Research, 2025)
Diarrheagenic Escherichia coli are the most common strains of E. coli that animals and humans are exposed to. It can be classified into six pathogenic groups, regarding their antibiotic resistance ability and the presence of virulence genes. Most of them are located on mobile genetic elements such as plasmids. Thus, this study aimed to identify the plasmid DNA patterns from E. coli isolated from dogs and humans each of which has diarrhoea. In order to search for similarities between the plasmids distributed among them, plasmid patterns as bands on agarose gel and plasmid incompatibility replicons detection were applied. A multiplex PCR-based method was used to detect the presence of the most common plasmid replicons (B/O, FIA, FIB, I1 and Frep). The results showed that almost all E. coli isolates contain plasmids. The IncF (FIA and FIB) replicons were the most prevalent Inc (60%) among human isolates. In contrast, the dominant Inc replicon in dog isolate was Frep followed by FIB and FIA in rates reached 35% and 25% respectively. Whereas, the 1I replicon was the least common in both sources. The dual plasmids Inc Frep+FIB and Frep+FIA were found to be the shared types. In contrast, one of the triple Incs patterns (FIB+Ferp+B/O) was common among dog and human isolates. This pattern’s similarity indicates the bacterial transmitted ability and triggered a preliminary idea about the possibility of plasmid transmission between E. coli from different hosts.